Question
Asked Dec 16, 2019
8 views

Checking to see if I did this right.

Solve the equation below for P
-p + 2) = -3 – p
p = - 10
P= 2
A,
help_outline

Image Transcriptionclose

Solve the equation below for P -p + 2) = -3 – p p = - 10 P= 2 A,

fullscreen
check_circle

Expert Answer

star
star
star
star
star
1 Rating
Step 1

First of all, open the brackets and add +p on both sides of the equation such that the unknown p is on LHS of the equation.

help_outline

Image Transcriptionclose

-(p+2) =-3-p 2 =-3 – p p-1=-3- p p+p-1=-3-p+p p+p-1=-3

fullscreen
Step 2

Then, add the two terms of p to get 1 term ...

help_outline

Image Transcriptionclose

p+p-1=-3 р+-хр-1- -3 2 -1+2 -хр-1%3-3 2 -p-1=-3

fullscreen

Want to see the full answer?

See Solution

Check out a sample Q&A here.

Want to see this answer and more?

Solutions are written by subject experts who are available 24/7. Questions are typically answered within 1 hour.*

See Solution
*Response times may vary by subject and question.
Tagged in

Math

Algebra

Equations and In-equations